Association between walking time spent and high sensitivity C-reactive protein level among obese women - Daud, Azlina; Abu Bakar Sedek, Siti Sarah Hasanah; Shahadan, Siti Zuhaidah (2018)
Introduction: Obesity has become the major health problem globally, and higher prevalence has been seen among women. High sensitivity C-reactive protein (hs-CRP) level is an inflammatory marker which is closely associated with obesity and cardiovascular disease (CVD). Increasing walking time spent can help reduce hs-CRP level and risk of developing cardiovascular disease. Aim: The objective of the study was to assess the association between walking time spent and hs-CRP level, to determine the risk of cardiovascular disease among obese women. Methods: A cross sectional study was conducted in Kuantan, Pahang. The purposive sampling method was chosen. A sample of 76 obese women aged 18 years old and above was included in the study. Data were collected using a self-reported questionnaire focused on socio demographic information and walking time over the previous seven days. A blood sample was taken in order to measure hs-CRP level. Result: Walking time spent in minutes was found to be significantly inversely associated with hs-CRP level (p = 0.040) among obese women. Conclusion: Increasing walking time spent can help reduce hs-CRP level, therefore reducing the risk of CVD.